The Effect of Education on Waste Management Activities 3R Method (Reduce, Reuse, Recycle) in RW 016 Pagambiran Ampalu Nan XX Village, Lubuk Begalung District, Padang City in 2023 - Shandy Rizky Bernanda; Darwel; Sri Lestari; Wijayantono; Afridon (CV. Get Press Indonesia, 2024)
The Padang City Environment Agency reported that the city generated an average of 643.76 tons of waste per day in 2021–2022. According to the head of RW 016, residents dispose of waste at the TPS due to limited available land. This study aims to assess the impact of education on 3R (Reduce, Reuse, Recycle) waste management in RW 016, Pagambiran Ampalu Nan XX Village, Lubuk Begalung District, Padang City, in 2023. A quantitative descriptive method was used with pretest and posttest assessments to measure knowledge levels. The paired sample t-test was employed for data analysis. The study involved 40 housewives as respondents, and data were collected through field observation and questionnaires. After data processing and analysis using frequency distribution tables, results showed a significant improvement in waste management knowledge after educational intervention. The mean score increased from 29.10 before education to 36.23 after, with a p-value of 0.000, indicating a statistically significant difference. These findings demonstrate that education positively influences 3R-based waste management behavior. To support sustainable waste practices, it is recommended that local government and village authorities provide adequate infrastructure such as segregated waste bins, recycling facilities, and environmentally friendly